HUBUNGAN ANTARA POSISI TUBUH SAAT BEKERJA TERHADAP KEJADIAN LOW BACK PAIN (LBP) PADA PETANI SAWIT - Remon ' '; Gamya Tri Utami; Ari Pristiana Dewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Safety at working area is still largely ignored by worker. Low back pain is the most frequent musculoskeletal complain. The aim of this research was to identify the correlation between the position of the body while working and incidence of low back pain (LBP) in farmers palm at village Kotalama subdistrict Kunto darussalam. The design was descriptive correlation research with cross sectional approach. The sampling technique was purposive sampling with inclusion criteria involving 109 respondents. This research used observation sheets that has been validity and reliability. The univariate analysis used to determine the frequency distribution, and The bivariat analysis used Chi-Square test. The results showed that there was a significant relationship between the position of the body while working and incidence of low back pain (LBP) on farmers palm with p value (0.000) < α (0.05). Based on this result , palm farmers should be more knowing about the right position of body while working to reduce low back pain incidence.   Keywords : Farmers palm, low back pain, position of the body.